Epithelial Membrane Antigen Expression in Various WHO Thymoma Types - Khoury, MD, Thaer (North American Journal of Medicine and Science, 2010)
Background: Epithelial membrane antigen (EMA) is a glycoprotein, widely used in the differential diagnosis of epithelial neoplasms. Little is known about EMA expression in thymic neoplasms classified based on world health organization (WHO) scheme. Material and Methods: A series of 66 thymic neoplasms were reviewed and classified according to the WHO scheme. These cases along with 7 normal thymic tissues were constructed in three tissue microarray blocks. Slides were stained using anti-EMA monoclonal antibody. Staining patterns were recorded for each tumor, as well as the staining intensity and percentage of stained tumor cells. In case of presence of more than one histologic type, staining was interpreted based on the predominant component.